COMPLEX TREATMENT OF LOCALLY ADVANCED MALIGNANT TUMORS OF THE THYROID GLAND WITH INVASION INTO THE ORGANS OF THE NECK AND MEDIASTINUM - Deineko, I.V. (World of Medicine and Biology, 2024)
Patients with locally advanced thyroid cancer require particular attention, as the selection of surgical techniques and a logical program of complex therapy for them remain controversial. Given the significant complexity and prevalence of fatal complications in cases of tumor stenosis of the upper airway during emergency tracheostomy, it is recommended that the patient be prepared for radical or palliative surgery in a prepared operating room in a planned manner with patient intubation, if possible. Given the high proportion of locally advanced, highly differentiated tumors that are refractory to radioiodine therapy and have a high malignant potential, as well as the poor prognosis associated with local recurrence of the disease, surgical intervention as part of a comprehensive treatment plan should be as radical and aggressive as possible, with macroscopic removal of the entire tumor, including all invasions of organs and tissues of the neck and mediastinum, especially in cases of medium and low-grade tumors. Conversely, when planning a traumatic surgery, it is essential to consider the patient’s general condition, age, and comorbidities. In cases where traumatic surgery is contraindicated, particularly in highly differentiated cancers, less radical methods of "shaving" the tumor without compromising the integrity of the organ may be employed.